Association between functional status and ocular surface disease among local elderly population in Hong Kong. (3rd October 2021) - Choy, Bonnie Nga Kwan; Pang, Jason Chun Sum; Zhu, Ming Ming; Ng, Alex Lap Ki; Chan, Jonathan Cheuk Hung; Fan, Michelle Ching Yim; Iu, Lawrence Pui Leung; Chiu, Patrick Ka Chun; Kwan, Joseph Shiu Kwong; Lai, Jimmy Shiu Ming
ABSTRACT: Purpose : To evaluate the correlation between ocular surface disease (OSD) and functional status among elderly population over 60 years old in Hong Kong. Methods : Chinese subjects above 60 years old were recruited from the Ophthalmology clinic in Hong Kong West Cluster. Subjects demographic and questionnaires to evaluate the functional status were used to correlate with OSD objectively with clinical examination to assess the meibomian gland dysfunction (MGD), corneal staining, Schirmer's test and tear break-up time (TBUT); and subjectively with ocular surface disease index (OSDI). Results : Twenty-eight patients were recruited, with a mean age of 71.5 ± 6.8 years. There was good correlation between the findings of the two eyes for bilateral measurements. Corneal staining was present in 75% of the subjects, while 92.9% of them had positive MGD grading. TBUT was reduced in 85.7% of the subjects. There is a negative association between MGD grading and Barthel index (r = −0.55, p < .01), indicating worse activities of daily living is related to worse MGD. OSDI is negatively associated with Schirmer's test (r = −0.49, p < .01). A negative correlation is also found between TBUT value and corneal staining (r = −0.58, p < .01). Conclusions : There is a high prevalence of OSD among our subjects. Lower Barthel index (indicating worse Lawton's instrumental activities of daily living) is associated with worse MGD grading. In elderly with poor functional status, care should be taken to manage their OSD.